Mobilisers Teacher Performance and its Impact on Learning Innovation - Nurmadiah, Nurmadiah (Indonesian Journal Education, 2024)
This research uses a descriptive qualitative approach to describe the performance of the mobiliser teacher role and its impact on learning innovation in schools. Purposively, 9 teachers of mobilisers and 4 ordinary teachers in public first schools were selected as respondents. The results of this study explain that the performance of driving teachers has an impact on teacher learning innovation. The performance of driving teachers is reflected in the existence of their effective role in developing teacher learning innovations. The findings of this study explain the performance of mobilising teachers based on their roles, namely (1) the role of leading learning; (2) become a coach for teachers; (3) encouraging collaboration; (4) realising student leadership; dan (5) mobilising communities of practice.